Laboratory and field test study on the improvement of marine clay slurry by in-situ solidification. Issue 6 (3rd July 2019) - Chen, Yonghui; Gao, Shihu; Chen, Long; Chen, Geng; Chen, Jianrong
Abstract: Soil solidification technology can create an artificial hard shell on a soft soil surface but the type and proportion of the curing agent, the construction technology, and the strengthening depth have large influences on the strengthening effect and engineering cost. This study introduces a new technology of soil solidification whereby an artificial hard shell layer is used as a new method to improve the soft ground. For the in-situ solidification technology, the soil and curing agent are mixed well by using a strong stirring machine so that the soil is strengthened rapidly and forms a hard crust. We introduce the key technology of the in-situ soil solidification method and determine the in-situ crust carrying capacity. The indoor experiment on the curing agent proportions is validated with field tests and a vane shear test, static penetration test, and plate loading test are used to evaluate the reinforcement effect. The experimental results show that the in-situ curing technology of dredged fill processing markedly reduced the reinforcement depth range of the soil water content, improved the physical and mechanical indices, and increased the bearing capacity and strength of the artificial hard shell layer, thereby fully meeting the requirements for the bearing capacity of construction machinery.